Synthesis and characterization of furfural-functionalized poly(vinyl alcohol) cross-linked with maleimide bearing tributyltin groups - Viorica Gaina; Oana Ursache; Constantin Gaina; Irina Rosca; Ana-Lavinia Vasiliu (eXPRESS Polymer Letters, 2022)
In the present work, new cross-linked networks based on furfural-functionalized poly(vinyl alcohol) (PVF) and maleimide compounds containing tributyltin groups were synthesized. The networks were obtained both as films and porous membranes. The structure of the compounds was confirmed by ATR-FTIR spectroscopy, and the morphology of the films/microporous membranes was investigated using scanning electron microscopy measurements (SEM), the differences between the films and membranes being evidenced. The mechanical performance and thermal stability of the membranes were examined by dynamic mechanical analysis (DMA) and thermogravimetry analysis (TGA), respectively. In addition, their water absorption and antimicrobial properties were thoroughly discussed. The antimicrobial activity of furfural-functionalized poly(vinyl alcohol) was significantly improved by its reaction with compounds containing tributyltin groups.